2015
DOI: 10.1038/ncomms9687
|View full text |Cite|
|
Sign up to set email alerts
|

Characterizing noise structure in single-cell RNA-seq distinguishes genuine from technical stochastic allelic expression

Abstract: SummarySingle-cell RNA-sequencing (scRNA-seq) facilitates identification of new cell types and gene regulatory networks as well as dissection of the kinetics of gene expression and patterns of allele-specific expression. However, to facilitate such analyses, separating biological variability from the high level of technical noise that affects scRNA-seq protocols is vital. Here we describe and validate a generative statistical model that accurately quantifies technical noise with the help of external RNA spike-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
216
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 235 publications
(229 citation statements)
references
References 28 publications
(49 reference statements)
8
216
0
Order By: Relevance
“…The problem of low sensitivity is amplified by the low capture rate of transcripts in single cell–gene expression analysis (typically 60% to 90% of transcripts of a given cell are lost) and by technical (sampling) noise [2527]. This can lead to false-positive sets of mutually exclusive expression of transcripts and thereby inflate cell-cell diversity, which is a crucial quantity in our analysis (S1 Appendix, A.8) [28]. …”
Section: Resultsmentioning
confidence: 99%
“…The problem of low sensitivity is amplified by the low capture rate of transcripts in single cell–gene expression analysis (typically 60% to 90% of transcripts of a given cell are lost) and by technical (sampling) noise [2527]. This can lead to false-positive sets of mutually exclusive expression of transcripts and thereby inflate cell-cell diversity, which is a crucial quantity in our analysis (S1 Appendix, A.8) [28]. …”
Section: Resultsmentioning
confidence: 99%
“…There are many other strategies for defining HVGs, e.g., by using the coefficient of variation ( Brennecke et al , 2013; Kim et al , 2015; Kolodziejczyk et al , 2015), with the dispersion parameter in the negative binomial distribution ( McCarthy et al , 2012), or as a proportion of total variability ( Vallejos et al , 2015). Some of these methods are available in scran – for example, see or for calculations based on the coefficient of variation.…”
Section: Analysis Of Haematopoietic Stem Cellsmentioning
confidence: 99%
“…Previously, our lab and others demonstrated that single-cell RNA-seq facilitates the identification of ASE patterns. [21][22][23][24] In this study, we sequenced the RNA of 1,084 single fibroblasts from 5 individuals. For 2 of these individuals, the parental DNA was available.…”
Section: Introductionmentioning
confidence: 99%